2020
DOI: 10.1177/0003489419901136
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Electrical and Tactile Sensitivity Changes After Middle Ear Surgery

Abstract: Objective/Hypothesis: Taste disturbances are often seen in patients after middle ear surgery due to the stress received by an unprotected chorda tympani. It has also been reported that loss in tactile sensitivity may accompany this issue. The current study was designed to measure electrical, chemical, and tactile sensitives of several senses involved in oral processing, smell, taste and touch, over time. Study Design: Prospective cohort study. Methods: For three time points, one before middle ear surgery and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…As expected, patients showed significantly reduced taste sensitivity in taste strips and electrogustometry testing, with threshold in patients being twice as high as in controls for all four regions of the tongue. Our results confirmed the strength of the electrogustometry analysis in detecting gustatory impairments 40 , 41 . In contrast, the whole mouth testing using supra-threshold taste sprays did not show any differences between the two groups.…”
Section: Discussionsupporting
confidence: 86%
“…As expected, patients showed significantly reduced taste sensitivity in taste strips and electrogustometry testing, with threshold in patients being twice as high as in controls for all four regions of the tongue. Our results confirmed the strength of the electrogustometry analysis in detecting gustatory impairments 40 , 41 . In contrast, the whole mouth testing using supra-threshold taste sprays did not show any differences between the two groups.…”
Section: Discussionsupporting
confidence: 86%
“…One study reported that EGM was better at detecting age-related decline in taste than taste strip test 28 . Another study found that EGM were more sensitive to deviations of taste and showed no signs of recovery in patients with taste impairment after middle ear surgery unlike taste strip test 29 . In the MDS analysis in this study, chemical taste test and EGM constituted a well-distinguished area.…”
Section: Discussionmentioning
confidence: 97%
“…To date, there is no consensus regarding which type of CTN injury, obtained during primary stapes surgery or cochlear implantation, leads to the least burden. Change in taste sensation can alter the enjoyment of food, which is a burden to the patient [2,3]. Some articles concluded that the taste outcome is better if the CTN is sacrificed instead of being preserved but damaged by stretching [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%